Upaya Komisi Pemilihan Umum Provinsi Sumatera Selatan dalam Meningkatkan Partisipasi Pemilih pada Pilkada Serentak 2018 dan Pemilu Serentak 2019 - Andi Chandra; Erik Darmawan; Yesi Yesi (Jurnal Studi Sosial dan Politik, 2018)
This study explains the efforts of the South Sumatra Provincial Election Commission in increasing the political participation of the people of South Sumatra in the 2018 Simultaneous Local Election and 2019 Concurrent Elections. Democracy is determined by the voice of the people, and is closely related to legitimacy "the fewer choose the lower legitimacy, the more they choose high legitimacy. "Legitimacy is very important because of the initial legitimacy of everything in the process of implementing power from the leader. The problem in this study is how the South Sumatra Provincial Election Commission's efforts in increasing community political participation in the 2018 simultaneous regional elections and 2019 simultaneous elections, and public response to the efforts made by the South Sumatra Provincial Election Commission. This study aims to describe the efforts of the KPU of South Sumatra Province and find out the public response to the efforts of the KPU of South Sumatra Province. Theoretically this research is useful to be a reference in the study of political science and is able to become a reference in future research related to the ongoing democracy in Indonesia and the practical benefits of being able to become input to the KPU of South Sumatra Province. The theory used by researchers is Max Weber's legitimacy theory where this theory explains how important participation is to legitimacy. By using descriptive type method and qualitative approach, the data obtained by using interviews, observation, and documentation. Researcher's location is at the KPU of South Sumatra Province. The results of the study show that the KPU of South Sumatra Province has made 350 efforts to increase the political participation of the people. The result prived that the political participation percentage in crease from 63% in 2013, 69,2% in 2018, and 81,42% in 2019. Efforts to increase people's political participation will continue to be increased.